Study of magnetofluidic laser scattering under rotating magnetic field - Pai, Chintamani (2018)
Magnetic field driven self-assembly of magnetic nanoparticles provides wireless programmable approach for tunable magnetofluidic laser scattering. In this work, we study magnetofluidic laser scattering from a commercial aqueous magnetic fluid (EMG 707) under an external rotating magnetic field. A set-up is developed to generate rotating magnetic field for the purpose. Self-assembled magnetic nanoparticle structures in the form of chains and bundles are formed along the magnetic field. This creates a linear streak formation in the forward laser scattering. Rotating magnetic field produces rotating linear streak. We report our initial results of rotating linear streaks at 3 rpm, 6 rpm and 10 rpm and our analysis of the patterns. The studies are useful for developing magnetic fluid based optical devices.